Pengaruh Jumlah Tanggungan, Pendapatan Usaha, dan Besar Pinjaman pada Tingkat Kelancaran Pengembalian Kredit - Pradnya Budi, Luh Ade Dyah; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 24 No 2 (2018)DO - 10.24843/EJA.2018.v24.i02.p10, 2018)
Micro Business Loan at BRI Unit Marga Tabanan is a government program that has an important role in providing capital assistance to MSMEs in Marga Tabanan. The purpose of this study is to determine the effect of the number of dependents, business income, and loan size on the smoothness of micro business credit repayment. The sample used in this research is micro business credit entrepreneurs BRI Unit Marga Tabanan. The sample was determined using a saturated sample so that 129 samples were obtained. Data were collected through survey method with questionnaire instrument. Data analysis technique used is multiple linear regression analysis. Based on the results of the study, the more the number of dependents the level of credit repayment smooth progressively lower. The higher the business income, the better the credit repayment rate. The higher the loan size the better the credit repayment rate